Implementasi Prinsip Syariah dalam Pengelolaan Keuangan melalui Produk Simpanan Umat: Studi Kasus KSPPS BMT Dana Mentari Muhammadiyah Purwokerto - Adibatunnisa Adibatunnisa; Zahra Ayu Agustin; Reifka Nur Amalia; Sulasih Sulasih (Rashid : Journal of Economic, 2025)
This study aims to analyze the implementation of sharia principles in managing the Simpanan Umat product at KSPPS BMT Dana Mentari Muhammadiyah Purwokerto and evaluate its contribution to institutional integrity, member trust, and community empowerment. Using a descriptive qualitative method, data were collected through semi-structured interviews, observations, and document studies involving management, staff, and members selected by purposive sampling. The data analysis followed the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The findings reveal that KSPPS BMT Dana Mentari consistently applies sharia principles—trustworthiness (amanah), justice, balance, and public interest—in operational activities. These values are reflected in transparent contracts, ethical fund management, member-centered services, and educational efforts that strengthen sharia literacy and accountability. This strategic approach ensures that financial activities not only achieve economic goals but also uphold spiritual and social values in accordance with Islamic ethical standards.